Analysis Wind Characteristics in South Lampung Indonesia - Rico Aditia Prahmana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
Many researchers have begun to evaluate the characteristics of the wind to be the mainstay of energy utilized for power generation. Various countries have started to conduct research of analysis the characteristics of wind potential in certain areas. In this study, wind speed data is be measured in the South Lampung. The maximum and minimum wind speed average in one day is 4.2 knot (from east to west direction) and 0.9 knot (from west to east direction), respectively. The sensor of wid speed is located at 10 meter height from ground. The results show that the maximum wind speed can reach 3 m/s at a height of 10 m on August and December. Moreover, the most wind direction during July to December goes to WSW (West SouthernWest) and SSE (South SouthernEast).